2016
DOI: 10.3945/jn.116.233676
|View full text |Cite
|
Sign up to set email alerts
|

A Retinol Isotope Dilution Equation Predicts Both Group and Individual Total Body Vitamin A Stores in Adults Based on Data from an Early Postdosing Blood Sample

Abstract: Background: Retinol isotope dilution (RID) is used to determine vitamin A total body stores (TBS) after an oral dose of a vitamin A stable isotope. The generally accepted prediction equation proposed by Olson’s group in 1989 (Furr et al. Am J Clin Nutr 1989;49:713–6) includes factors related to dose absorption and retention, isotope equilibration in plasma compared with stores, catabolism during the mixing period, and the optimal time for measuring plasma isotope enrichment.Objectives: The objectives were 1) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…In conclusion, the application of model-based compartmental analysis has the potential to provide unique information and insights into vitamin A and β-carotene kinetics and metabolism as well as practical results with the potential for application in the field. For example, in the accompanying article in this issue ( 26 ), we used modeling results to modify the original retinol isotope dilution equation ( 27 ) for predicting total body vitamin A stores on the basis of a single, early blood sample. Similarly, our current modeling results confirm graphical methods for estimating β-carotene bioefficacy and may lead to a simpler method that will be useful in the field.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the application of model-based compartmental analysis has the potential to provide unique information and insights into vitamin A and β-carotene kinetics and metabolism as well as practical results with the potential for application in the field. For example, in the accompanying article in this issue ( 26 ), we used modeling results to modify the original retinol isotope dilution equation ( 27 ) for predicting total body vitamin A stores on the basis of a single, early blood sample. Similarly, our current modeling results confirm graphical methods for estimating β-carotene bioefficacy and may lead to a simpler method that will be useful in the field.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to SA p , RID equations include coefficients that account for absorption and retention of the dose and mixing of tracer with the body pool. Here we used the RID equation presented by Green et al ( 21 ), shown below as Equation 2 , to predict TBS for individual subjects: \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}\begin{eqnarray*} {\rm{TBS}}\left( {\rm{\mu}} {\rm{mol}} \right) = Fa \times S \times 1/{\rm{S}}{{\rm{A}}_{\rm{p}}} \end{eqnarray*}\end{document} where Fa is the fraction of dose of labeled vitamin A absorbed and found in the body's storage pool at time t , S is the ratio of retinol specific activity in plasma to that in the storage pool at time t , and SA p was calculated as FD p ÷ plasma retinol pool size (µmol) at time t . In empirical studies, one would calculate SA p as [tracer ÷ (tracer + tracee)] ÷ dose (µmol) in plasma at time t .…”
Section: Methodsmentioning
confidence: 99%
“…We used Equation 2 as follows to predict TBS in individual children at the time (4 d) that is currently being used in the ongoing field studies. First, for each protocol, we simulated values for the time-variant coefficients Fa and S at 4 d using the population model (for details on the calculation of equation coefficients by the model, see references 14 and 21 and Supplemental Methods). Population estimates for the composite coefficient Fa × S were then used in Equation 2 , along with each theoretical child's SA p at 4 d, to predict TBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The changing fraction of the dose in the serum is mathematically modeled by constructing several theoretical compartments within the body by using kinetic constants that describe the movement of retinol throughout the body and its irreversible degradation. Attempts have been made to use this model to develop RID equations that could be applied as early as 3–5 d postdose by estimating the ratio of isotopic enrichment of retinol in plasma and stores reached in the body at any given time ( 47 † , 48 † ). Some studies make use of a composite model (i.e., “super child” or “super woman”) in which data points from multiple subjects, who each contribute to a fraction of the total number of time points, are combined to form a population-level compartmental model ( 49 † , 50 ).…”
Section: Current Status Of Knowledgementioning
confidence: 99%